Chemiluminescence of Mn-Doped ZnS Nanocrystals Induced by Direct Chemical Oxidation and Ionic Liquid-Sensitized Effect as an Efficient and Green Catalyst - Azizi, Seyed Naser; Chaichi, Mohammad Javad; Shakeri, Parmis; Bekhradnia, Ahmadreza; Taghavi, Mehdi; Ghaemy, Mousa (Journal of Spectroscopy, 2013)
A novel chemiluminescence (CL) method was proposed for doping water-soluble Mn in ZnS quantum dots (QDs) as CL emitter. Water-soluble Mn-doped ZnS QDs were synthesized by using L-cysteine as stabilizer in aqueous solution. These nanoparticles were structurally and optically characterized by X-ray powder diffraction (XRD), dynamic light scattering (DLS), Fourier transform infrared spectroscopy (FTIR), UV-Vis absorption spectroscopy, and photoluminescence (PL) emission spectroscopy. The CL of ZnS QDs was induced directly by chemical oxidation and its ionic liquid-sensitized effect in aqueous solution was then investigated. It was found that oxidants, especially hydrogen peroxide, could directly oxidize ZnS QDs to produce weak CL emission in basic solutions. In the presence of 1,3-dipropylimidazolium bromide/copper, a drastic light emission enhancement was observed which is related to a strong interaction between Cu2+ and the imidazolium ring. In these conditions, an efficient CL light was produced at low pH which is suggested to be beneficial to the biological analysis. The CL properties of QDs not only will be helpful to study physical chemistry properties of semiconductor nanocrystals but also they are expected to find use in many fields such as luminescence devices, bioanalysis, and multicolor labeling probes.